A Survey on Females’ Constraints in Physical Recreation Participation: 調查阻礙女性參與康體活動的因素 - CHEUNG, Pui Yee (Asian Journal of Physical Education & Recreation, 2005)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Female of all age groups and socio-economic status do face a number of constraints in pursuing physical recreation activity. The present paper aimed to study the constraints of female’s physical recreation participation, and the relationship of perceived constraints and the level of participation between different occupation status, education level, and marital status. Two hundred and eight females aged 18 to 60 were invited to fill in the Physical Recreation Participation Questionnaire (PRPQ) to identify their perceived constraints and level of physical recreation participation. Results indicated that there were certain constraints factors, such as psychological constraints, accessibility constraints and time constraints, more related to the constriction in female physical recreation participation. When analyzing the constraint dimensions with different status towards participation frequency, the result was not necessary negatively related. Only housewives and middle education level women with lower perceived constraints demonstrated higher physical recreation participation than their counterparts. 在參與康樂性質的體能活動時，無論年紀多大或有何種社會地位，女性均會面對不同的參與阻礙，本研究旨在了解其中的參與阻礙與女性的職業、敎育水平及婚姻狀況的關係。208位女士被邀請填寫「參舆體育康樂活動問卷」(PAPQ)。結果顯示心理因素、場地因素及時間因素為主要的參與阻礙；但是，參與阻礙與參與頻率並沒有呈反相關。另外，經常參與活動的家庭主婦及中等程度學歷的女士均面對較低的參與阻礙。